Frequency transformation in the auditory lemniscal thalamocortical system - Imaizumi, Kazuo; Lee, Charles C. (Frontiers in Neural Circuits, 2014)
The auditory lemniscal thalamocortical (TC) pathway conveys information from the ventral division of the medial geniculate body to the primary auditory cortex (A1). Although their general topographic organization has been well characterized, functional transformations at the lemniscal TC synapse still remain incompletely codified, largely due to the need for integration of functional anatomical results with the variability observed with various animal models and experimental techniques. In this review, we discuss these issues with classical approaches, such as in vivo extracellular recordings and tracer injections to physiologically identified areas in A1, and then compare these studies with modern approaches, such as in vivo two-photon calcium imaging, in vivo whole-cell recordings, optogenetic methods, and in vitro methods using slice preparations. A surprising finding from a comparison of classical and modern approaches is the similar degree of convergence from thalamic neurons to single A1 neurons and clusters of A1 neurons, although, thalamic convergence to single A1 neurons is more restricted areas within putative thalamic frequency lamina. These comparisons suggest that frequency convergence from thalamic input to A1 is functionally limited. Finally, we consider synaptic organization of TC projections and future directions for research.